Preventing thrombosis in a COVID‐19 patient by combined therapy with nafamostat and heparin during extracorporeal membrane oxygenation. Issue 1 (6th December 2020) - Doi, Shunichi; Akashi, Yoshihiro J.; Takita, Mumon; Yoshida, Hideki; Morikawa, Daiki; Ishibashi, Yuki; Higuma, Takumi; Fujitani, Shigeki
Abstract : Background: Preventing thrombosis in extracorporeal membrane oxygenation (ECMO) can be life‐saving in cases of coronavirus disease (COVID‐19); however, circuit thrombosis is a complication. This report describes a COVID‐19 patient treated with nafamostat and heparin to prevent circuit thrombosis during ECMO support. Case presentation: A 63‐year‐old man was transferred to our hospital with respiratory failure due to COVID‐19 pneumonia. He was provided venous‐venous ECMO to maintain oxygenation. During ECMO support, occlusive circuit thrombosis developed despite systemic anticoagulation therapy with heparin. He was subsequently given combination therapy with nafamostat and heparin. Although the combination therapy could prevent circuit thrombosis, it was converted to heparin monotherapy because of hyperkalemia and hemothorax. After tracheostomy and a gradual improvement in oxygenation, ECMO was discontinued. He was transferred to another hospital for further rehabilitation. Conclusion: Combination therapy with nafamostat and heparin can prevent circuit thrombosis during ECMO. However, bleeding can still develop with this combination therapy during ECMO. Abstract : This report describes a COVID‐19 patient treated with nafamostat and heparin to prevent circuit thrombosis during extracorporeal membrane oxygenation (ECMO) support. Combination with nafamostat and heparin might prevent circuit thrombosis in ECMO.